The Extracellular Matrix and the Tumor Microenvironment - Kovalszky, Ilona; Franchi, Marco; Alaniz, Laura D. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book introduces the most important and best studied extracellular and pericellular molecules of the tumor microenvironment. It gives a comprehensive overview of their role in tumor development and cancer progression. Twelve chapters deal with the biochemical and biophysical background of extracellular matrix (ECM) changes in the tumor stroma compared to the physiological state. The reader learns about the major ECM components that are deregulated during cancer development and how they are associated with cancer progression associated with survival, inflammation process, among others. These are followed by recent data about the cooperative activity of extracellular matrix in tumor metabolism, promoting cancer progression. Two chapters focus specifically on the critical role of the ECM in tumor angiogenesis, linking this process to cellular infiltration and metastatic behavior of tumors. The final part describes how the ECM influences the success of immuno- and chemotherapy in cancer patients, its potential as biomarkers for diagnosis, prognosis, and therapeutic target, as well as the mechanism of resistance-associated changes in the ECM. This book is an interesting read for anyone who want to know more about ECM and cancer biology. Early career scientists can use it as an introduction to the field, offering an excellent tool for studying ECM. Advanced researchers and clinicians can gain a broader overview of the subject, considering the role of ECM for influencing every cancer hallmark as well as in the response of cancer treatments. The work serves to inspire future research and shows that the ECM should be considered as an important factor in the development of cancer therapeutics. The series "Biology of Extracellular Matrix" is published in collaboration with the American Society for Matrix Biology and the International Society for Matrix Biology.
Chapter 1: Small leucine-rich proteoglycans regulate cancer cell growth, apoptosis-and associated inflammation -- Chapter 2: The role of decorin in cancer -- Chapter 3: The mystery of syndecan-1 in tumor development and progression -- Chapter 4:Syndecan-2 Biology and its Role in Colorectal Carcinoma -- Chapter 5: Versican in Tumor Progression, Tumor-Host Interactions and Cancer Immunotherapy -- Chapter 6:Circulating proteoglycans/glycosaminoglycans as cancer biomarkers -- Chapter 7: Hyaluronan in the Extracellular Matrix of hematological and solid tumors. Its biological effects" -- Chapter 8: Heparanase: a paramount enzyme for cancer initiation, progression and metastasis -- Chapter 9: Laminins and matrix metalloproteinases connection: a subtle relationship that can go wrong in a tumor context, particularly if CD44 gets involved -- Chapter 10:Basement membrane, collagen, and fibronectin: physical interactions with cancer cells -- Chapter 11: Integrins in cancer: re-focusing on the tumor microenvironment -- Chapter 12: Adipose compounds in breast tumor extracellular matrix -- Chapter 13: Extracellular matrix as a metabolic niche in cancer -- Chapter 14: The role of inflammatory cells in tumor angiogenesis -- Chapter 15: Cancer angiogenesis and its master regulator perlecan -- Chapter 16: The microRNA-extracellular matrix interplay in breast cancer -- Chapter 17: The impact of the extracellular matrix on immunotherapy success -- Chapter 18: Exploiting hyaluronan-CD44 network in tumor therapy.
Keywords: Cancer; Cytology; Clinical biochemistry; Cancer Biology; Cell Biology; Medical Biochemistry